A Theoretical Study of Pulmonary Capillary Gas Exchange and Venous Admixture - Milhorn, Howard T. (1968)
A model of pulmonary capillary gas exchange and venous admixture is presented and the inclusion of this model into a model of the entire respiratory system is discussed. Partial pressure and concentration gradients for nitrogen, helium, oxygen, and carbon dioxide are predicted. The cases of breathing room air and 10% oxygen are studied. In both of these studies the Bohr and Haldane effects are included, and the “physiological” dissociation curves of oxygen and carbon dioxide are predicted for the normal case as blood flows from the venous blood end of the capillary to the arterial blood end. Venous admixture effects are also calculated for both of these cases. The effects of emphysema, pulmonary congestion, and altered cardiac function on the gradients are studied.